ANALISIS KWALITAS WEBSITE LAYANAN ASPIRASI & PENGADUAN MASYARAKAT TANGKAR (TANGGAP KARAWANG) DI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN KARAWANG MENGGUNAKAN METODE WEBQUAL 4.0 - Teguh Prisma Herliana (INFOTECH journal, 2023)
and usage from the community's perspective towards the website is the reason why this research is conducted. Community satisfaction is one of the factors or measures of success for any information system development in a government. Good service quality is not only based on the perspective or perception of the service provider, but also based on the perspective or perception of the community. The community that enjoys the service is the community that can determine service quality. The community's perception of service quality is a comprehensive assessment of the excellence of a service. WebQual 4.0 is a method for determining website quality based on community or user perception. The WebQual 4.0 method consists of three categories, namely usability, information quality, and service interaction. These three categories are used as a reference in creating a questionnaire to analyze the quality of the community aspiration and complaint service website. The analysis results are expected to provide recommendations for local governments in developing quality websites so that the development of community aspiration and complaint service websites in Indonesia can mature, stabilize and ultimately reach a level of utilization.